2022
DOI: 10.1021/acscatal.2c02892
|View full text |Cite
|
Sign up to set email alerts
|

Access to Enantioenriched 1,n-Diamines via Ni-Catalyzed Hydroamination of Unactivated Alkenes with Weakly Coordinating Groups

Abstract: Enantioenriched 1,2- and 1,3-diamines with chiral α-branched aliphatic amine motifs are important substructures in bioactive compounds and related molecules and serve as privileged chiral ligands in both organo- and transition-metal-catalysis. However, direct access to such structural motifs remains a formidable challenge. Herein, a straightforward method to access 1,n-diamines (n = 2, 3, 4) containing a chiral α-branched aliphatic amine is achieved by Ni-catalyzed asymmetric hydroamination of unactivated alip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…In 2022, Shu et al [19] . developed a nickel‐catalyzed selective hydrogen amination reaction of alkenes to synthesize 1,3‐diamines (Scheme 12a).…”
Section: Intermolecular 13‐diamination Reactionmentioning
confidence: 99%
“…In 2022, Shu et al [19] . developed a nickel‐catalyzed selective hydrogen amination reaction of alkenes to synthesize 1,3‐diamines (Scheme 12a).…”
Section: Intermolecular 13‐diamination Reactionmentioning
confidence: 99%
“…Moreover, the enantioselec- tive syntheses of chiral 1,2-diamines and 1,3-diamines have also been established. Very recently, Hong et al 16 and Shu et al 17 reported an enantioselective hydroamination of allylic amines and homoallylic amines without migration. However, the migratory αor β-selective hydroamination and enantioselective migratory β-selective hydroamination have not been reported yet.…”
mentioning
confidence: 99%
“…Ether solvents, such as THF, were found to preferably promote the amination at initial olefinic sites (entry 7 vs entry 8). 16,17 Eventually, after extensive studies, we noticed that the addition of 10 mol % coligand PMe 3 further improved the enantioselectivity of 3-β to 93% with moderate yield (entry 9), which was proposed to suppress the background nonasymmetric reaction. 19 Fortu-nately, selective formation of γ-amination has proven to be possible, as the use of chiral dibenzyl-substituted Ph-Box ligand L6 in THF delivered 3-γ in 89% yield with 92% ee (entry 11).…”
mentioning
confidence: 99%
“…More importantly, aryl and alkenyl chlorides remains an unmet challenge. As our continuous effort on Ni-catalyzed selective transformations, we herein report the rapid synthesis of (hetero)­aryl and vinyl iodides via Ni-catalyzed Finkelstein reaction from (hetero)­aryl and vinyl halides (Scheme c). The use of a bisoxazoline ligand facilitates halogen exchange and reductive elimination, enabling the reaction proceed under mild conditions (mostly at room temperature) with broad functional group tolerance.…”
mentioning
confidence: 99%
“…Based on previous literature precedent of nickel or copper-catalyzed halogen exchange reactions, a plausible mechanism is proposed in Scheme . ,, The coordination between ligand and Ni­(COD) 2 would generate L -Ni­(0) complex A . The oxidative addition of 1 to A could form Ni­(II) intermediate B .…”
mentioning
confidence: 99%